Twist1 accelerates tumour vasculogenic mimicry by inhibiting Claudin15 expression in triple‐negative breast cancer. Issue 13 (29th May 2020) - Zhang, Danfang; Sun, Baocun; Zhao, Xiulan; Sun, Huizhi; An, Jindan; Lin, Xian; Zhu, Dongwang; Zhao, Xueming; Wang, Xudong; Liu, Fang; Zhang, Yanhui; Liu, Jiameng; et al.
Abstract: The up‐regulation of EMT regulator Twist1 has been implicated in vasculogenic mimicry (VM) formation in human triple‐negative breast cancer (TNBC). Twist1 targets the Claudin15 promoter in hepatocellular carcinoma cells. Claudin family members are related with TNBC. However, the relationship between Claudin15 and VM formation is not clear. In this study, we first found that Claudin15 expression was frequently down‐regulated in human TNBC, and Claudin15 down‐regulation was significantly associated with VM and Twist1 nuclear expression. Claudin15 down‐regulation correlated with shorter survival compared with high levels. Claudin15 silence significantly enhanced cell motility, invasiveness and VM formation in the non‐TNBC MCF‐7 cells. Conversely, an up‐regulation of Claudin15 remarkably reduced TNBC MDA‐MB‐231 cell migration, invasion and VM formation. We also showed that down‐regulation of Claudin15 was Twist1‐dependent, and Twist1 repressed Claudin15 promoter activity. Furthermore, GeneChip analyses of mammary glands of Claudin15‐deficient mice indicated that Claudin18 and Jun might be downstream factors of Twist1‐Claudin15. Our results suggest that Twist1 induced VM through Claudin15 suppression in TNBC, and Twist1 inhibition of Claudin15 might involve Claudin18 and Jun expression.